2011
DOI: 10.1080/01900692.2011.583770
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Turnover in the Omani Public Sector: An Islamic Values Perspective

Abstract: Following four decades of economic growth the public sector in Oman is experiencing an emerging problem of labour turnover to the private sector. We examine this phenomenon through semi-structured interviews with 26 current and former public employees. The rate of turnover is low but this masks the impact of losses to key technical and management roles.The main reasons for turnover are dissatisfaction with management style, reward practices and promotion opportunities. Findings are interpreted in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Researchers have revealed that younger Omani employees exhibit lower affective commitment and normative commitment than their older counterparts [4]. Swailes and Al Fahdi [5] revealed that dissatisfaction with management style has been impacting Omani public employees. It has also been found that immediate superiors have a robust impact on their subordinates' work performance [6; 7; 8].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have revealed that younger Omani employees exhibit lower affective commitment and normative commitment than their older counterparts [4]. Swailes and Al Fahdi [5] revealed that dissatisfaction with management style has been impacting Omani public employees. It has also been found that immediate superiors have a robust impact on their subordinates' work performance [6; 7; 8].…”
Section: Introductionmentioning
confidence: 99%
“…Often the individuals' perception of their prospects for generating a higher level income from private sector organizations can drive to leaving a public sector organizations. There is extensive research into turnover intentions, (e.g., see Bluedorn 1982b;Swailes and Fahdi 2011;Carmeli and Weisberg 2006;Nyberg 2010).…”
Section: Determinants Of the Intention To Leave An Organizationmentioning
confidence: 99%
“…According to semi-structured interviews with 260 current and former public employees conducted by Swailes and Al Fahdi (2011), participants regardless of their gender and age revealed concerns about the lack of praise or recognition, as interviewees believe that they do not receive enough support from HRM department, whether material or moral support, or even at least a word of thanks. They said that this affects their morale, and therefore their loyalty, as 77% are looking for another job, also, some stressed that HRM department is interested only in getting closer to the senior management, and never cares about the problems of employees.…”
Section: Human Resource Researchmentioning
confidence: 99%